Low Temperature and High Vapour Pressure Deficit Risks to Cool Season Crops in the Sub-tropics - Ram, Daya; Singh, Phool (Annals of Arid Zone, 2016)
Low temperature and high vapour pressure deficit risks has been made by using cumulative percentage frequency distribution method for judicious crop planning in cool season on the basis of 24 year (1971.72 to 1593-94) meteorological data for Hisar, India. During the period, January 1 to 28, the risk of <20C temperature at the screen 1-1 to 65%. ’his may reduce crop growth. Tile risk of vapour pressure deficit (>35 at the ear emergence/anthesis stage, emerging from 19th March to 2nd April is 50 ! As such, for the Hirar area, eulrivars that reach double "dgelfloral bud mitiation 28th Janualy and maturily/hamsting beforc 19th March, may bc selected. ?Be date wing is suggested as